Students views on the inclusion of multicultural perspectives into the psychology curriculum at two South African universities : an Afrocentric analysis. - Chitindingu, Ethel. (2012)
This research investigated students‘ views on the inclusion of multicultural perspectives into the psychology curriculum at two South African universities.54 students from the University of KwaZulu-Natal (UKZN) and a university in the Gauteng province participated in the research. The age of the participants ranged from 20-40 years. Purposive sampling was used to collect the data. Using a competency scale adjusted to suit a South African context participants were asked their views on a) the practice and supervision of psychology b) diversity in student representation c) students were also asked to rate how competent they were in multicultural issues d) research considerations e) if the physical environment reflected diversity. The students were of the view that South African universities have not adequately incorporated multicultural issues, African perspectives in particular, into the curriculum. The recommendations for future research, including curriculum transformation, are highlighted. === Thesis (M.Soc.Sc.)-University of KwaZulu-Natal, Pietermaritzburg, 2012.